FACTORS INFLUENCING WOMEN’S KNOWLEDGE OF BREAST CANCER: LITERATURE REVIEW - Andre Budi; Lady Evelyn Aritonang; Hendrianto (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Breast cancer remained the most frequently diagnosed cancer among women and continued to contribute substantially to morbidity and mortality, particularly in developing countries. In Indonesia, most breast cancer cases were detected at an advanced stage, indicating inadequate knowledge and low awareness of early detection. This study aimed to identify factors influencing women’s knowledge of breast cancer through a systematic literature review. A literature review was conducted using the Preferred Reporting Items for Systematic Reviews. Ten national and international research articles published between 2021 and 2025 were analyzed using a qualitative descriptive approach supported by simple descriptive statistics through vote counting. The results showed that women’s knowledge of breast cancer was influenced by internal and external factors. Internal factors included education level, age, attitudes and awareness, and psychological factors. External factors comprised access to information and educational media, the role of health professionals, educational interventions, socioeconomic status, cultural norms, and family support. Education level and access to information were identified as the most dominant factors based on their frequency across the reviewed studies. It was concluded that women’s knowledge of breast cancer was shaped by the interaction between individual characteristics and social environments. Comprehensive and sustainable health education strategies were therefore required to improve breast cancer awareness and support early detection practices.